Possible Role of Interleukin-6 in Rheumatoid Arthritis - Al-Haidary, Batool A. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Rheumatoid Arthritis (RA) is an autoimmune disease. Many etiological agents are proposed to play a role in its pathogenecity. One of these factors is cytokines such as Interleukin6.Material & Methods: ELISA method has been used for IL-6 estimation in 75 RA patients in comparison with 61 SLE as patient controls and 39 apparently healthy controls.Results: This study showed that there was an elevation of IL-6 in the sera of RA patients with high significant differences between RA patients and controls (P< 0.001). Moreover a good correlation between IL-6 level & RF titer were observed. However, for most patients with high IL-6 were shown to be HLA-DR4.Conclusions: Interleukin-6 play a crucial role in the disease which may be participate in the severity of RA & subsequently its treatment.